2007
DOI: 10.1093/hmg/ddl486
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β signaling alterations and susceptibility to colorectal cancer

Abstract: In 2006, more than 55,000 patients died of colorectal cancer in the US, accounting for approximately 10% of all cancer deaths. Despite significant progress in screening combined with the development of novel effective therapies, colorectal cancer ranks second to lung cancer as a cause of cancer death. Twin studies indicate that 35% of all colorectal cancers are inherited, but high-penetrance tumor susceptibility genes only account for approximately 3-6% of all cases. The remainder of the unexplained familial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
211
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(219 citation statements)
references
References 58 publications
(73 reference statements)
1
211
0
7
Order By: Relevance
“…Moreover, MCF-7 cells overexpressing Smad3 were more sensitive to ellagic acid. Previous studies have suggested that SMAD mutation and dysfunction plays an important role in the development of tumors (Tian et al, 2003;Leaslc and Abraham, 2004;Xu and Pasche, 2007;Su et al, 2010). Some downstream targets of the TGF-β signaling pathway are key regulators of cell cycle progression, including p21, p27 and p15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MCF-7 cells overexpressing Smad3 were more sensitive to ellagic acid. Previous studies have suggested that SMAD mutation and dysfunction plays an important role in the development of tumors (Tian et al, 2003;Leaslc and Abraham, 2004;Xu and Pasche, 2007;Su et al, 2010). Some downstream targets of the TGF-β signaling pathway are key regulators of cell cycle progression, including p21, p27 and p15.…”
Section: Discussionmentioning
confidence: 99%
“…Some downstream targets of the TGF-β signaling pathway are key regulators of cell cycle progression, including p21, p27 and p15. The activation of these genes will suppress tumor cell growth (Xu and Pasche, 2007). SIS3 is a specific inhibitor of Smad3 phosphorylation without affecting Smad2 and Smad4 (Jinnin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the enhancer of zeste homologue 2 (EZH2) protein was recently shown to downregulate RUNX3 expression by increasing histone H3 methylation, thus providing yet another mechanism for inactivation of RUNX3 (Fujii et al, 2008). As might be expected, if RUNX3 were behaving as a tumour suppressor, the decreased expression of this protein in gastric (Wei et al, 2005), lung (Araki et al, 2005) and oesophageal (Sakakura et al, 2007) cancers has been associated with worse patient outcome.As the TGF-b signalling pathway plays an important role in the growth control of human colonic epithelial cells (Xu and Pasche, 2007), RUNX3 may also act as a tumour suppressor gene in this tissue. Approximately 20% of primary CRCs show hypermethylation of RUNX3 (Goel et al, 2004;Ogino et al, 2007), and this has been linked to transcriptional silencing in two studies (Goel et al, 2004;Ku et al, 2004).…”
mentioning
confidence: 99%
“…As the TGF-b signalling pathway plays an important role in the growth control of human colonic epithelial cells (Xu and Pasche, 2007), RUNX3 may also act as a tumour suppressor gene in this tissue. Approximately 20% of primary CRCs show hypermethylation of RUNX3 (Goel et al, 2004;Ogino et al, 2007), and this has been linked to transcriptional silencing in two studies (Goel et al, 2004;Ku et al, 2004).…”
mentioning
confidence: 99%
“…Une fois activée, cette dernière phosphoryle les facteurs de transcription Smad2 et Smad3, leur permettant de se complexer à Smad4, qui est nécessaire à la translocation nucléaire du complexe. Le complexe Smad2/3/4 s'associe avec d'autres protéines telles que p21 ou la survivine pour les réguler [11]. Cette voie de signalisation doit être désactivée pour la progression tumorale des cellules coliques.…”
Section: Les Mutations Du Tgfbr2 Et De P53 : Progression Vers Le Cancunclassified